Which Winegrape Varieties are Grown Where? A Global Empirical Picture - Anderson, Kym (University of Adelaide Press, 2013)
In an increasingly interconnected world wine market, evolving consumer demands, technologies, and climate have all contributed to large shifts in global patterns of production and consumption of wine. These shifting patterns of wine production and consumption have entailed changes in the vineyard in terms of total area planted, production practices, and the mix of grape varieties grown. In this book, for the first time, we have a detailed empirical picture, country by country and region by region within countries, of which varieties of grapes have been grown where, and how those varietal choices have changed over time. This statistical compendium will be directly useful for anyone interested in knowing about and understanding the changing patterns of production of wine and wine grapes around the world. It also will serve as an invaluable resource for economists and others who seek to analyze those patterns and their causes